2013
DOI: 10.2196/jmir.2427
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Patients Toward Adoption of 3D Technology in Pain Assessment: Qualitative Perspective

Abstract: BackgroundPast research has revealed that insufficient pain assessment could, and often, has negative implications on the provision of quality health care. While current available clinical approaches have proven to be valid interventions, they are expensive and can often fail in providing efficient pain measurements. The increase in the prevalence of pain calls for more intuitive pain assessment solutions. Computerized alternatives have already been proposed both in the literature and in commerce, but may lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Similar results were obtained in the treatment of panic disorder with or without agoraphobia ( Botella et al, 2007 ). In the case of the assessment and treatment of pain, patients have also shown high acceptance of the introduction of technology, and they have very positively appraised the use of technologies, highlighting that these tools could have a positive influence on the treatment outcomes ( Spyridonis et al, 2013 ). In the same way, preliminary data in patients who suffer from stress-related disorders indicate high levels of satisfaction with the use of VR ( Baños et al, 2009 ; Andreu-Mateu, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained in the treatment of panic disorder with or without agoraphobia ( Botella et al, 2007 ). In the case of the assessment and treatment of pain, patients have also shown high acceptance of the introduction of technology, and they have very positively appraised the use of technologies, highlighting that these tools could have a positive influence on the treatment outcomes ( Spyridonis et al, 2013 ). In the same way, preliminary data in patients who suffer from stress-related disorders indicate high levels of satisfaction with the use of VR ( Baños et al, 2009 ; Andreu-Mateu, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“… 38 , 68 For example, a more detailed, gender-specific manikin may enable women to better communicate their pain, 69 with potential for improving their health care and outcomes. 70 However, personalisation requirements may vary between people depending on their age, gender and ethnicity. This adds complexity of implementing such requirements into manikin software and warrants careful consideration of if and how such modifications impact the usability, reliability and validity of digital manikins as a pain measurement instrument.…”
Section: Discussionmentioning
confidence: 99%
“…A 3D visualization of the environment is constructed, with the help of the robot, to assist clinicians in identifying the precise location and nature of extrinsic fall hazards. Examples in other areas of health care include the work of Spyridonis et al [ 34 ] who found that enabling patients to carry out self-assessments by reporting the type and precise location of back pain by using a 3D visualization of the human body was more accurate and intuitive than the traditional paper-based 2D model of the human body typically used in practice. Other studies have found similar benefits in utilizing 3D visualizations to communicate other forms of pain to clinicians.…”
Section: Introductionmentioning
confidence: 99%